2015
DOI: 10.1007/s11431-015-5912-2
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of unconfined turbulent swirling flow

Abstract: Large eddy simulations (LES) were performed to study the non-reacting flow fields of a Cambridge swirl burner. The dynamic Smagorinsky eddy viscosity model is used as the sub-grid scale turbulence model. Comparisons of experimental data show that the LES results are capable of predicting mean and root-mean-square velocity profiles. The LES results show that the annular swirling flow has a minor impact on the formation of the bluff-body recirculation zone. The vortex structures near the shear layers, visualized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The addition of swirl has a significant impact on the flow structures in the initial merging region of an annular jet. If a very small amount of swirl is added, the Kelvin-Helmholtz instability in the inner and outer shear layers becomes helical (Garcia-Villalba, Frohlich & Rodi 2006;Jones, Lyra & Navarro-Martinex 2012;Zhang et al 2015) and the meandering of the wake at zero swirl transforms into a precession (Vanierschot & Van den Bulck 2011;Vanierschot et al 2014). As the level of swirl is further increased, these helical instabilities become stronger.…”
mentioning
confidence: 99%
“…The addition of swirl has a significant impact on the flow structures in the initial merging region of an annular jet. If a very small amount of swirl is added, the Kelvin-Helmholtz instability in the inner and outer shear layers becomes helical (Garcia-Villalba, Frohlich & Rodi 2006;Jones, Lyra & Navarro-Martinex 2012;Zhang et al 2015) and the meandering of the wake at zero swirl transforms into a precession (Vanierschot & Van den Bulck 2011;Vanierschot et al 2014). As the level of swirl is further increased, these helical instabilities become stronger.…”
mentioning
confidence: 99%
“…In the present work, the 2-step global mechanism for methane oxidation is selected to handle the combustion and the chemical reactions are formulated as equations (15) and (16). Two sets of Arrhenius parameters are adopted to describe the chemical kinetics, one for the 2sCM2 scheme [37] (referred to as Mech I) and the other for the Arrhenius parameter-optimized 2-step scheme (referred to as Mech II) reduced based on the GRI 3.0.…”
Section: Chemical Kineticsmentioning
confidence: 99%
“…Velocity and major species profiles showed good agreement with experimental data, whilst local temperature profiles had slight discrepancies in the central regions for swirling cases. Zhang et al [16] simulated both reacting and nonreacting SwB cases to assess different LES SGS models. Dynamic thickened flame combined with the FGM tabulation approach (DTF-FGM) and presumed PDF combined with the FGM approach (PPDF-FGM) were used to model premixed flame and stratified flame, where flame features and unsteady large-scale structure behaviors were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al 37 simulated turbulent confined swirling annular flows using LES to study the behavior of the large-scale coherent structures formed by the high levels of swirl. Zhang et al 38 found that the helical structure associated with the PVC is the most energetic dynamic flow structure in the non-reacting flow fields of a Cambridge swirl burner by performing LES. In addition, LES was utilized to asses the capability of Reynolds-averaged Navier-Stokes simulations on predicting helical instabilities in swirling flows [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%